Impact of CeO2 nanoparticles and crude walnut oil-diesel blends on combustion, performance, and emission characteristics of a diesel engine - Hazar, Hanbey; Akcay, Can; Sevinc, Huseyin (Pergamon-Elsevier Science Ltd, 2025)
The search for sustainable alternatives to diesel fuel is challenged by performance losses and increased emissions when using crude vegetable oils, due to their high viscosity and low volatility. This study addresses this limitation by investigating the usability of crude walnut (Juglans regia L.) oil and nanoparticle mixtures as an alternative fuel in a diesel engine. Crude walnut oil was blended with diesel fuel at three volumetric rates (10 %, 20 %, and 40 %), and cerium oxide (CeO2) nanoparticles (50 ppm) were incorporated into the blends. To improve physicochemical properties, preheating treatment at 70 degrees C was applied to the crude walnut oil blends. Engine tests were performed on a single-cylinder diesel engine under constant speed and varying load conditions. The results showed that the addition of crude walnut oil increased carbon monoxide (CO), hydrocarbons (HC), smoke density, exhaust gas temperature (EGT) and brake specific fuel consumption (BSFC) values and decreased nitrogen oxides (NOX) emission, noise and vibration values. Preheating improved emission characteristics but slightly increased noise and vibration. Addition of CeO2 generally showed an improvement effect on CO, HC, smoke density, and BSFC values. A 10 % preheated crude walnut oil blend with CeO2 lowered exhaust emissions while maintaining engine performance comparable to diesel fuel. This work is novel in combining a non-edible vegetable oil with oxygen-storage-capable nanoparticles, a rarely explored approach that enhances combustion efficiency and lowers emissions. Preheating with nanoparticle addition further reduces the drawbacks of crude walnut oil, supporting its use as a cleaner and more efficient diesel alternative.
Keywords: Diesel engine; Emissions; Performance; Raw walnut oil; Cerium oxide; Preheating